PENGARUH PERILAKU WAJIB PAJAK TERHADAP KEPATUHAN DALAM MEMBAYAR PAJAK (Students' Journal of Accounting and Banking, 2013)
Amount Taxpayers year by year progressively increase, but there are constraint able to pursue the improvement effort tax ratio, the constraint is compliance of taxpayer. This research test the factors influence of the storey level compliance of taxpayer by using some the variables have been used by theX the researcher before all, that is awareness of tax, service of fiskus, and penalty of sanction. Population in this research is the taxpayer in KPP Pratama Candisari Semarang. Intake sampel done with method random sampling and obtained by 75 responder, but the data in processing in this research is 50 responder. Method data collecting of primary the weared is enquette method ( kuesioner). Technique analyse the data the used is doubled linear regression. Hypothesis in this research tested by using doubled linear regression. Pursuant to the analysis done, hence obtained conclusion that awareness of tax, service of fiskus, sanction of penalty the taxpayer have an effect on positive signifikan to compliance of taxpayer.Keywords: compliance of taxpayer, awareness of tax, service of fiskus, sanction of penalty